DERMATOGLYPHIC CHARACTERIZATION OF BULGARIAN POPULATION FROM SOME REGIONS OF SOUTHEASTERN BULGARIA: DERMATOGLYPHIC CHARACTERIZATION OF BULGARIAN POPULATION FROM SOME REGIONS OF SOUTHEASTERN BULGARIA - Minkov, Tzvetan; Boichev, Milen; Todorov, Velislav; Paraskova, Nadejda; Georgiev, Volodia; Boycheva, Maria; Vassilev, Angel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Finger and palm patterns of Bulgarian population from the regions of Liubimets and Svilengrad were studied. The dermatoglyphic features of 102 men and 95 women from the region of Liubimets and 91 men and 105 women from the region of Svilengrad have been investigated. It was established, that by the complex of dermatoglyphic features, the studied population from both regions is too homogenous and belongs to one and the same population.